Zirconium alloy powders for manufacture of 3D printed articles used in nuclear power industry - Ianko, T.; Panov, S.; Sushchyns’ky, O.; Pylypenko, M.; Dmytrenko, O. (Вопросы атомной науки и техники, 2018)
Main methods of zirconium alloy powder synthesis have been reviewed. Powder applications for additive manufacturing were analyzed. Advantages and drawbacks of zirconium powder production and usage have been shown. Hydrogenation/dehydrogenation method was offered for zirconium powder production. Розглянуто основні способи отримання порошків цирконієвих сплавів. Проаналізовано застосування порошків в адитивних виробництвах. Показано переваги та недоліки способів отримання і застосування порошків цирконію. Для виробництва порошків цирконію запропоновано метод гідрування/дегідрування. Рассмотрены основные способы получения порошков циркониевых сплавов. Проанализированы применения порошков в аддитивных производствах. Показаны преимущества и недостатки способов получения и применения порошков циркония. Для производства порошков циркония предложен метод гидрирования/дегидрирования.